2022
DOI: 10.1037/cns0000291
|View full text |Cite
|
Sign up to set email alerts
|

Toward a theory of conscious–nonconscious processing and getting hard (and easy) things done in everyday life.

Abstract: Much of everyday life consists of obligatory long-term behaviors, from work itself to doing dishes. Although some activities (e.g., exercise) are harder than others, even the seemingly easy activities can turn into hard ones when repeated monotonously day after day. It is proposed that this paradox has its roots in two fundamental human tendencies: (a) following the path of least resistance and (b) avoiding monotony, boredom, and even stimulus deprivation. How does the human mind operate in the presence of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 130 publications
1
9
0
Order By: Relevance
“…As such, results supported a 2-vector theory of leisure motivation (Iso-Ahola, 1989, 2022, according to which people use leisure to seek personal rewards from engagement and to simultaneously escape personal problems and the routine environment (not just work) on one hand and to use leisure to seek interpersonal rewards by doing things with friends but simultaneously escaping or leaving the routine interpersonal world behind on the other. In other words, leisure engagement brings meaning to people's lives, because it enables them to pursue personal rewards in skillful activities and interpersonal rewards in social interaction with friends, but also at the same time allows them to escape or leave behind every day personal issues and usual interpersonal contacts.…”
Section: Seeking Versus Escapingsupporting
confidence: 59%
“…As such, results supported a 2-vector theory of leisure motivation (Iso-Ahola, 1989, 2022, according to which people use leisure to seek personal rewards from engagement and to simultaneously escape personal problems and the routine environment (not just work) on one hand and to use leisure to seek interpersonal rewards by doing things with friends but simultaneously escaping or leaving the routine interpersonal world behind on the other. In other words, leisure engagement brings meaning to people's lives, because it enables them to pursue personal rewards in skillful activities and interpersonal rewards in social interaction with friends, but also at the same time allows them to escape or leave behind every day personal issues and usual interpersonal contacts.…”
Section: Seeking Versus Escapingsupporting
confidence: 59%
“…Similarly for humans, only engaging in a small number of games with their cats may lead guardians to experience boredom and dissatisfaction with play, potentially resulting in guardians playing less with their cats. It has previously been found that routine behaviours, which a person feels obligated to perform, undermine their sense of self and freedom (Iso-Ahola 2022 ). However, these negative aspects can be mitigated by increasing the variety in, and of, these behaviours, such as undertaking a variety of different activities that achieve the same purpose (Iso-Ahola 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been found that routine behaviours, which a person feels obligated to perform, undermine their sense of self and freedom (Iso-Ahola 2022 ). However, these negative aspects can be mitigated by increasing the variety in, and of, these behaviours, such as undertaking a variety of different activities that achieve the same purpose (Iso-Ahola 2022 ). Tasks that require too little cognitive engagement (such as repeating the same wand toy game with a cat) also can become boring and aversive, leading people to either disengage with the task or seek to enhance variety and novelty (Shenhav et al .…”
Section: Discussionmentioning
confidence: 99%
“…When he/she leaves the day’s work behind, he/she continues this balancing act between leisure and work. Although nonconscious repeating makes task completion more efficient and cognitively less demanding, evidence suggests that people seek to “repeat with variety” either by switching activities or adding elements of variety within an activity already undertaken (Iso-Ahola, 2022a). In this way, the interplay of conscious and nonconscious processing gets everyday tasks completed and rewarding experiences had.…”
Section: What Is a Psychological Phenomenon?mentioning
confidence: 99%